Studio Mumbai 2003-2011 : maneras de hacer y de fabricar. (Madrid : El Croquis, 2011)
Studio Mumbai is a human infrastructure of skilled craftsmen and architects who design and build the work directly. Gathered through time, this group shares an environment created from an iterative process, where ideas are explored through the production of large-scale mock-ups, models, material studies, sketches and drawings. Projects are developed through careful consideration of place and a practice that draws from traditional skills, local building techniques, materials and an ingenuity arising from limited resources. The practice was started in 1995 by Bijoy Jain. Projects include the Studio Mumbai Work-Place in Nagaon, the Casa Tara in Kashid, the Leti 360 Resort in Leti, the Palmyra House in Nandgaon. Excerpts from a dialogue between Dr. Balkrishna V. Doshi and Bijoy Jain and an essay by Peter Wilson.
Keywords: Ambachten; Bouwmaterialen; Duurzaam bouwen; India; Natuur in de architectuur